Multiferroic Electroactive Polymer Blend/Ferrite Nanocomposite Flexible Films for Cooling Devices - Casagrande-Denardin, J (American Chemical Society, 2023)
In recent days, the interest toward the development of multicaloric materials for cooling application is increasing, whereas multiferroic materials would be the suitable alternative to the conventional refrigerants. To explore them, the poly(methyl methacrylate)/poly(vinylidenefluoride-co-hexafluoropropylene) (PMMA/PVDF-HFP) blend and PMMA/PVDF-HFP/Zn0.5Cu0.5Fe2O4 flexible multiferroic nanocomposite films were fabricated by the solution casting method. The structural analyses prove that the strong interfacial interaction between the PMMA/PVDF-HFP blend and the Zn0.5Cu0.5Fe2O4 (ZCF) through hydroxyl (−OH) and carbonyl group bonding with PVDF-HFP enhanced the thermal stability and suppressed the electroactive β phase from 67 to 62%. Experimental results show that 10 wt % of superparamagnetic ZCF nanoparticles with a particle size of 6.8 nm induced both the magnetocaloric and magnetoelectric effects in a nonmagnetic PMMA/PVDF-HFP ferroelectric matrix at room temperature. A set of isothermal magnetization curves were recorded in the magnetic field strength of 0-40 kOe and a temperature range of 2-400 K. The maximum magnetic entropy changes (ΔSM) of −0.69 J·kg-1 K-1 of ZCF nanoparticles and −0.094 J·kg-1 K-1 of PMMA/PVDF-HFP/ZCF nanocomposites showed an interesting table-like flat variation in the temperature range of 100-400 K as a function of the magnetic field. The samples display a large temperature span with a relative cooling power of 293 and 40 J·kg-1 for ZCF and PMMA/PVDF-HFP/ZCF, respectively. The magnetoelectric effect of the PMMA/PVDF-HFP/ZCF composite was proved, but it generated only 1.42 mV/m·Oe in the applied field of 5 kOe. Hence, the entropy change of the present nanocomposite was only due to the magnetocaloric effect, where the magnetoelectric cross-coupling coefficient was negligible. The multicaloric effect could be established if the nanocomposite showed a larger magnetoelectric cross-coupling in addition to the magnetocaloric effect. This approach provides the research findings in functional multiferroic polymer nanocomposites for miniaturized cooling devices. © 2023 American Chemical Society.